Intra-procedural pain score in a randomised controlled trial comparing mechanochemical ablation to radiofrequency ablation: The Multicentre Venefit™ versus ClariVein® for varicose veins trial. (February 2016) - Bootun, R; Lane, TRA; Dharmarajah, B; Lim, CS; Najem, M; Renton, S; Sritharan, K; Davies, AH
Objective: Endovenous techniques are, at present, the recommended choice for truncal vein treatment. However, the thermal techniques require tumescent anaesthesia, which can be uncomfortable during administration. Non-tumescent, non-thermal techniques would, therefore, have potential benefits. This randomised controlled trial is being carried out to compare the degree of pain that patients experience while receiving mechanochemical ablation or radiofrequency ablation. The early results of this randomised controlled trial are reported here. Methods: Patients attending for the treatment of primary varicose veins were randomised to receive mechanochemical ablation (ClariVein®) or radiofrequency ablation (Covidien® Venefit™). The most symptomatic limb was randomised. The primary outcome measure was intra-procedural pain using a validated visual analogue scale. The secondary outcome measures were change in quality of life and clinical scores, time to return to normal activities and work as well as the occlusion rate. Results: One-hundred and nineteen patients have been randomised (60 in the mechanochemical ablation group). Baseline characteristics were similar. Maximum pain score was significantly lower in the mechanochemical ablation group (19.3 mm, standard deviation ±19 mm) compared to the radiofrequency ablation group (34.5 mm ± 23 mm; p  < 0.001). Average pain score was also significantly lower in the mechanochemical ablation group (13.4 mm ± 16 mm) compared to the radiofrequency ablation group (24.4 mm ± 18 mm; p  = 0.001). Sixty-six percent attended follow-up at one month, and the complete or proximal occlusion rates were 92% for both groups. At one month, the clinical and quality of life scores for both groups had similar improvements. Conclusion: Early results show that the mechanochemical ablation is less painful than the radiofrequency ablation procedure. Clinical and quality of life scores were similarly improved at one month. The long-term data including occlusion rates at six months and quality of life scores are being collected.